The Space of the City and Literary Imagination: the Legacy of Nikolai Antsiferov (ENTHYMEMA, 2014)
This paper discusses the legacy of Nikolai Antsiferov (1889–1958), a Russian historian who suggested a unique approach to urban studies in which literature played the key role. In the first section of this paper, the genesis of Antsiferov’s conceptions of the study of urban history and the image of the city are outlined. The second section provides an analysis of his ideas on the literary image of St. Petersburg and the theory of literary-themed guided tours, which were articulated in his works of the 1920s. The finalsection of the article sheds light on the reception and legacy of Antsiferov’s intellectual ideas in the modern humanities and assesses its significance in the modern context of interdisciplinarity.